2021
DOI: 10.48550/arxiv.2105.11139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can we distinguish astrophysical from primordial black holes via the stochastic gravitational wave background?

Suvodip Mukherjee,
Joseph Silk

Abstract: One of the crucial windows for distinguishing astrophysical black holes from primordial black holes is through the redshift evolution of their respective merger rates. The low redshift population of black holes of astrophysical origin is expected to follow the star formation rate. The corresponding peak in their merger rate is going to peak at a redshift smaller than that of the star formation rate peak (z p ≈ 2), depending on the time delay between the formation and mergers of black holes. Black holes of prim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Meanwhile, the required abundance of PBHs were found to be compatible with the existing upper limits from other observations. The inferred upper limits were shown to be close to the existing upper limits, implying that such scenarios can be further tested by observations of stochastic gravitational-wave background (SGWB) in the near future [25][26][27][28][29]. In addition, we found that the mass function of PBHs with m * = 5.4M and σ = 0.54 almost simultaneously explains the observed merger rates of GW200105 and GW200115, including the center values and error bars.…”
Section: Discussionsupporting
confidence: 74%
“…Meanwhile, the required abundance of PBHs were found to be compatible with the existing upper limits from other observations. The inferred upper limits were shown to be close to the existing upper limits, implying that such scenarios can be further tested by observations of stochastic gravitational-wave background (SGWB) in the near future [25][26][27][28][29]. In addition, we found that the mass function of PBHs with m * = 5.4M and σ = 0.54 almost simultaneously explains the observed merger rates of GW200105 and GW200115, including the center values and error bars.…”
Section: Discussionsupporting
confidence: 74%
“…An independent way to infer the PISN mass distribution is using the cross-correlation technique after marginalizing over the GW bias parameters (Mukherjee & Wandelt 2018;Mukherjee et al , 2021bDiaz & Mukherjee 2021). A proper inference of the mass distribution of the BBHs will also be useful for the analysis of the stochastic GW background (Mukherjee & Silk 2020; Callister et al 2020;Mukherjee & Silk 2021;Mukherjee et al 2021a) and lensing event rates (Oguri 2018;Mukherjee et al 2021e). The amplitude of the stochastic GW background and also the lensing event rates strongly depend on the mass distribution of the BBHs.…”
Section: Impact On Gw Source Population Inference and Cosmologymentioning
confidence: 99%
“…In this paper, we estimate the SGWB signal from subsolar mass compact objects, and the possibility of detection via upcoming gravitational wave detectors. By exploring the evolution of the merger rate of the subsolar sources and their mass distribution, we will be able to distinguish between sources of primordial origin and astrophysical origin as proposed by [43]. Along with the SGWB, individual events can also shed light on the existence of subsolar PBHs [38][39][40]44].…”
mentioning
confidence: 99%